2016
DOI: 10.1016/j.ihj.2015.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of early direct current cardioversion for maintenance of sinus rhythm in rheumatic atrial fibrillation following successful balloon mitral valvotomy

Abstract: In patients with rheumatic MS and AF, early DCCV and a short-duration oral Amiodarone, following successful PBMV, may be a reasonable strategy to attain long-term SR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Benefits of restoring SR include symptomatic relief, improved exercise capacity and quality of life, possible reduction in embolic strokes and improved survival. 14 , 15 , 18 , 28 We also observed significant improvement in NYHA class and QOL scores in patients who were in SR as compared to those with persistent AF. Predictors of successful outcomes at 1 year were shorter duration of AF (<3.5 years) and smaller left atrial size (<51 mm).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Benefits of restoring SR include symptomatic relief, improved exercise capacity and quality of life, possible reduction in embolic strokes and improved survival. 14 , 15 , 18 , 28 We also observed significant improvement in NYHA class and QOL scores in patients who were in SR as compared to those with persistent AF. Predictors of successful outcomes at 1 year were shorter duration of AF (<3.5 years) and smaller left atrial size (<51 mm).…”
Section: Discussionsupporting
confidence: 54%
“…Reported success rates vary from 38% using only pharmacological conversion with oral amiodarone 13 ; performing DCCV in patients pre-administered oral or IV amiodarone is known to further improve success rates to 55–96% (maintenance of SR at 1 year follow up). 14 , 15 , 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One small randomised study evaluated the efficacy of early DCCV along with intravenous loading dose followed by low-dose short duration (100 mg/day during 6 weeks) amiodarone after successful PMC 36. At the end of a short follow-up period (range 6–9 months), 13/15 (87%) patients remained in SR, while 2 patients (13%) had reverted to AF, one at 2 weeks and one at 4 months.…”
Section: Medical Therapies Of Af and Its Complicationsmentioning
confidence: 99%
“…Vora et al [17] compared the rhythm control strategy with amiodarone versus rate control with diltiazem in patients with rheumatic AF and noted that patients treated with the rhythm control strategy presented a significant improvement in functional class, exercise capacity, and quality of life score compared with patients treated with the rate-control strategy. Sharma et al [18] randomized patients with rheumatic MS after balloon mitral valvotomy to the rhythm control strategy by electrical cardioversion followed by oral amiodarone versus placebo and found that patients in the rhythm control arm had a significantly better quality of life at the end of 6 months than those in the placebo arm.…”
Section: Discussionmentioning
confidence: 99%